Meminimalisir Resiko Perubahan Valuta Asing Melalui Lindung Nilai (Hedging) Terhadap PT. Petrosea Tbk - Sholahuddin Shariawi; Maria Yunita Tianar Br Panjaitan; Alfin Nathanael (Politeknik Negeri Padang, 2023)
The Petrosea Tbk. (PTRO) is one of the most experienced multi-national companies in Indonesia. This company is engaged in mining contracting, construction, pawning and providing service contracts for supporting oil and gas (Oil and Gas) which have the aim of advancing activities in the ESG (Environment, social, governance) aspect as a decision on the sustainability of the Company. PT Petrosea Tbk. (PTRO) was established on February 21, 1972. The purpose of this study was to determine the effect of hedging on Derivative financial instruments in foreign currencies. This research was conducted by PT. Petrosea, Tbk by using a Research Method, namely a Descriptive Method which aims to find a solution to the problem being investigated through a description of the condition of the subject and object that occurs. which as stipulated in PSAK No.71 (2020, Tarko), Hedging is also carried out by several companies such as: PT. Sarana Infrasktur Indonesia & PT. Multi Infrastructure Facilities (2020, Ministry of Finance).From the results of research conducted on the company's analysis, it can be concluded that PT. Petrosea Tbk (PTRO) is transacting using foreign currency.